Chest wall mass with fistula to the skin, caused by a ruptured amebic liver abscess. Issue 45 (January 2022) - Lin, Geng-Lou; Tai, Chien-Hsiang; Lee, Chen-Hsiang; Lee, Ing-Kit
Highlights: Amebiasis in developed countries is mostly in returning travelers or immigrants. Transmission occurs after ingestion of contaminated food or water. Amebiasis could cause colitis and even liver abscess. The variables of presentations of amebiasis makes the diagnosis very challenging. Once a correct diagnosis is made, most patients recover fully with proper treatment.